Assessment of mitochondrial energy coupling in vivo by (13)C/(31)P NMR - Jucker, Beat M. (National Academy of Sciences, 2000)
The recently cloned uncoupling protein homolog UCP3 is expressed primarily in muscle and therefore may play a significant role in the regulation of energy expenditure and body weight. However, investigation into the regulation of uncoupling protein has been hampered by the inability to assess its activity in vivo. In this report, we demonstrate the use of a noninvasive NMR technique to assess mitochondrial energy uncoupling in skeletal muscle of awake rats by combining (13)C NMR to measure rates of mitochondrial substrate oxidation with (31)P NMR to assess unidirectional ATP synthesis flux. These combined (31)P/(13)C NMR measurements were performed in control, 10-day triiodo-l-thyronine (T(3))-treated (model of increased UCP3 expression), and acute 2,4-dinitrophenol (DNP)-treated (protonophore and mitochondrial uncoupler) rats. UCP3 mRNA and protein levels increased 8.1-fold (± 1.1) and 2.8-fold (± 0.8), respectively, in the T(3)-treated vs. control rat gastrocnemius muscle. (13)C NMR measurements of tricarboxylic acid cycle flux as an index of mitochondrial substrate oxidation were 61 ± 21, 148 ± 25, and 310 ± 48 nmol/g per min in the control, T(3), and DNP groups, respectively. (31)P NMR saturation transfer measurements of unidirectional ATP synthesis flux were 83 ± 14, 84 ± 14, and 73 ± 7 nmol/g per s in the control, T(3), and DNP groups, respectively. Together, these flux measurements, when normalized to the control group, suggest that acute administration of DNP (mitochondrial uncoupler) and chronic administration of T(3) decrease energy coupling by ≈80% and ≈60%, respectively, and that the latter treatment correlates with an increase in UCP3 mRNA and protein expression. This NMR approach could prove useful for exploring the regulation of uncoupling protein activity in vivo and elucidating its role in energy metabolism and obesity.